Substantial Decline in Prevalence of Vaccine-Type and Nonvaccine-Type Human Papillomavirus (HPV) in Vaccinated and Unvaccinated Girls 5 Years After Implementing HPV Vaccine in Norway. (16th July 2018) - Feiring, Berit; Laake, Ida; Christiansen, Irene Kraus; Hansen, Mona; Stålcrantz, Jeanette; Ambur, Ole Herman; Magnus, Per; Jonassen, Christine Monceyron; Trogstad, Lill
Abstract : High HPV vaccine uptake in a single-cohort program aimed at largely HPV-naive girls reduced vaccine types by 90% in vaccinated and 54% in unvaccinated girls. Indication of cross-protection in both vaccinated and unvaccinated girls was also observed. Abstract: Background: In 2009, quadrivalent human papillomavirus (HPV) vaccine was introduced in a school-based single-cohort program targeting 12-year-old girls in Norway. We estimated the impact of the Norwegian HPV immunization program. Methods: Three birth cohorts of 17-year-old girls, 2 nonvaccine-eligible cohorts (born 1994 or 1996) and 1 vaccine-eligible cohort (born 1997) were invited to deliver urine samples. The samples were analyzed for 37 HPV genotypes. HPV prevalence was compared between birth cohorts and between vaccinated and unvaccinated girls within and across birth cohorts after linkage to the Norwegian Immunisation Registry. Results: In total, 17749 urine samples were analyzed. A 42% (95% confidence interval [CI], 37%–47%) reduction in any HPV type and 81% (95% CI, 76%–85%) reduction in vaccine types (HPV-6/11/16/18) were observed in the vaccine-eligible cohort compared to the 1994 cohort. Vaccine types were reduced by 54% (95% CI, 39%–66%) and 90% (95% CI, 86%–92%) in unvaccinated and vaccinated girls, respectively, from the 1997 cohort, compared with unvaccinated girls born in 1994. A significant reduction was also observed for several nonvaccine types. Vaccine-type prevalence was reduced by 77% (95% CI, 65%–85%) in vaccinated compared with unvaccinated girls from the 1997 cohort. Conclusions: In this largely HPV-naive population, we observed a substantial reduction in vaccine and nonvaccine types in vaccinated and unvaccinated girls following introduction of HPV vaccination.